Differential Immunotoxicity Induced by Two Different Windows of Developmental Trichloroethylene Exposure. (20th February 2014) - Gilbert, Kathleen M.; Woodruff, William; Blossom, Sarah J.
Abstract : Developmental exposure to environmental toxicants may induce immune system alterations that contribute to adult stage autoimmune disease. We have shown that continuous exposure of MRL+/+ mice to trichloroethylene (TCE) from gestational day (GD) 0 to postnatal day (PND) 49 alters several aspects of CD4 + T cell function. This window of exposure corresponds to conception-adolescence/young adulthood in humans. More narrowly defining the window of TCE developmental exposure causes immunotoxicity that would establish the stage at which avoidance and/or intervention would be most effective. The current study divided continuous TCE exposure into two separate windows, namely, gestation only (GD0 to birth (PND0)) and early-life only (PND0-PND49). The mice were examined for specific alterations in CD4 + T cell function at PND49. One potentially long-lasting effect of developmental exposure, alterations in retrotransposon expression indicative of epigenetic alterations, was found in peripheral CD4 + T cells from both sets of developmentally exposed mice. Interestingly, certain other effects, such as alterations in thymus cellularity, were only found in mice exposed to TCE during gestation. In contrast, expansion of memory/activation cell subset of peripheral CD4 + T cells were only found in mice exposed to TCE during early life. Different windows of developmental TCE exposure can have different functional consequences.